Efektivitas Media Visual Flipbook Peta dalam Meningkatkan Pemahaman Siswa pada Materi IPS Kelas VI - Mariska, Nova; Nurazizah, Salma Tasya; Rahmadani, Mabda; Fitri, Alfia Nur; Nugraha, Rana Gustian (YASIN, 2025)
Although visual learning media have been widely examined in social studies education, research that specifically investigates the integration of a digital flipbook format with spatial map visualization to address the spatial literacy crisis among elementary school students remains limited. This study aims to empirically test and analyze the effectiveness of the Media Visual Flipbook Peta in improving sixth-grade students’ understanding of IPS content, particularly related to spatial and geographical concepts. A quantitative approach with a one-group pretest–posttest experimental design was employed, involving 22 sixth-grade students at SDN Citengah selected through saturated sampling. Data were collected using pretest and posttest instruments and analyzed using the Wilcoxon Signed Rank Test, paired t-test, and Normalized Gain (N-Gain). The results show a statistically significant increase in understanding, as evidenced by the Wilcoxon test (p = 0.000) and paired t-test (p = 0.000), with the mean score increasing from 95.45 to 99.09 and the standard deviation decreasing from 8.18 to 4.33, indicating a more homogeneous distribution of understanding. The N-Gain value of 0.381 (38.1%) falls within the medium effectiveness category and is influenced by a ceiling effect, as 77.27% of students had already achieved the maximum score on the pretest. These findings contribute to the development of the Cognitive Theory of Multimedia Learning (CTML) in the context of primary education and deepen understanding of the integration of interactive digital media to enhance spatial literacy. The study concludes that the Media Visual Flipbook Peta is important for improving conceptual understanding and equalizing students’ levels of understanding in spatial social studies content and recommends that educators and curriculum developers adopt multimodal and interactive digital media for teaching abstract concepts. The implications include theoretical contributions to the educational technology and multimedia instructional design literature, as well as practical implications for elementary schools, teachers, and policymakers to invest in the development of digital learning media and teacher capacity building in technology integration, while opening avenues for further exploration of long-term retention, affective and psychomotor dimensions, and replication in student populations with more diverse initial ability levels.